2023
DOI: 10.1021/acsnano.2c12269
|View full text |Cite
|
Sign up to set email alerts
|

Elasto-Plastic Design of Ultrathin Interlayer for Enhancing Strain Tolerance of Flexible Electronics

Abstract: The ability to tolerate large strains during various degrees of deformation is a core issue in the development of flexible electronics. Commonly used strategies nowadays to enhance the strain tolerance of thin film devices focus on the optimization of the device architecture and the increase of bonding at the materials interface. In this paper, we propose a strategy, namely elasto-plastic design of an ultrathin interlayer, to boost the strain tolerance of flexible electronics. We demonstrate that insertion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 66 publications
(96 reference statements)
0
16
0
Order By: Relevance
“…Recently, Zheng et al reported a new strategy, namely elastoplastic design of an ultrathin interlayer, to reduce the bending strain of flexible electronic device. [132] An interlayer with high Young's modulus and high yield strain is inserted between the rigid electronic device and the soft substrate. The bending strain and the density of microcracks of the device are reduced when the interlayer is more elastic than the upper electronic devices.…”
Section: Foldable El Devicesmentioning
confidence: 99%
“…Recently, Zheng et al reported a new strategy, namely elastoplastic design of an ultrathin interlayer, to reduce the bending strain of flexible electronic device. [132] An interlayer with high Young's modulus and high yield strain is inserted between the rigid electronic device and the soft substrate. The bending strain and the density of microcracks of the device are reduced when the interlayer is more elastic than the upper electronic devices.…”
Section: Foldable El Devicesmentioning
confidence: 99%
“…Very recently, a new material principle on elasto‐plastic interlayer design was proposed for the material optimization of the ultrathin interlayer for enhancing the strain tolerance of the device. [ 92 ] It was found that the interlayer with both high Young's modulus and high‐yield strain can reduce the actual strain on the upper rigid film in deformation. Experiments were carried out for the investigation of the crack behavior and electrical resistance change of the Cu film on a plastic substrate coated with different types of interlayers, e.g., polymethyl methacrylate (PMMA), Cr, and Cu‐polymer nanocomposite, which was fabricated through polymer‐assisted metal deposition (PAMD), [ 142–147 ] These interlayers have different elastoplastic material properties, and thus show different strain tolerance, which is in good agreement with the principle.…”
Section: Structural Design In the Vertical Directionmentioning
confidence: 99%
“…Elasto‐plastic design image: Reproduced with permission. [ 92 ] Copyright 2023, American Chemistry Society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced physicochemical and electrochemical sensing principles, along with emerging sensing modalities and inventive machine learning strategies, have showcased remarkably sensitive and multifunctional electronics. Recent advances in stretchable and luminescent materials, optical sensing, and electronic devices have also laid the foundation for the development of wearable optical devices. These devices offer a wide range of potential applications, including monitoring biophysical and biochemical indicators, detecting muscle or joint movements, and recognizing occlusal patterns for human–computer interaction. , …”
mentioning
confidence: 99%